Yields, Forage Characteristics, and Nutritive Values of Purple Guinea Grass and Mombasa Guinea Grass at Different Cutting Ages - Thongruang, Saranpong; Manatrinon, Supawadee; Swangkit, Takkavit; Kochasopon, Sopon (Journal of Mahanakorn Veterinary Medicine, 2021)
The objective of this research was to compare the yields, forage characteristics and nutritive values of Mombasa guinea grass (Panicum maximum cv. Mombasa) and Purple guinea grass (Panicum maxicum TD58). Mombasa guinea grass was very similar to Purple guinea grass, but was resistant to leaf spot disease. The experimental design was 2x3 factorial in CRD. The factor 1 were species of grass (Purple guinea and Mombasa guinea grass) and factor 2 were cutting ages (30, 45 and 60 days) with 3 replications. It was found that the interaction between grass species and cutting ages resulted in significantly different (P<0.05) in leaf/stem ratio. Mombasa guinea grass at 30 days of cutting age had the highest leaf/stem ratio (37.48±3.36) whereas Mombasa (11.11±1.22) and Purple guinea (10.95±1.84) grass at 60 days of cutting age had the lowest leaf/stem ratio. Mombasa guinea grass had significantly (P<0.05) higher tiller height, crude protein and ADL than those of Purple guinea grass while yields, tiller number, tiller diameter, crude fat, ash, crude fiber, NDF and ADF of Mombasa guinea and Purple guinea grass were not significantly different (P>0.05). Therefore, Mombasa guinea grass at 30 days of cutting was planted in Phetchaburi soil series was the most suitable for feeding the animals due to appropriated yields and had higher forage characteristics and crude protein than those of Purple guinea grass.